Effects of Hypoxic and Normoxic Training in Altitude on HIF-1α and PGC-1α Levels in Elite Endurance Runners - Rahman Soori; Mahla Mohamad Zadeh; Amine Ghram; Siroos Choobineh; Roohallah Mohammadi Mirzaei; Fabrício Azevedo Voltarelli (Sport Sciences and Health Research)
Introduction: Training at altitude or in a hypoxic environment has gained attention among athletes, coaches, and scientists to enhance sea-level performance. However, the efficacy of “Living-Low, Training-High, Training-Low” (LLTHTL) strategy to escalate the mechanisms associated with enhancing performance in the human athletes is still unknown. The present study aimed to investigate the effect of the LLTHTL on Hypoxia-Inducible Factor-1 alpha (HIF-1α) and peroxisome Proliferator-activated Receptor-Gamma Coactivator-1alpha (PGC-1α) levels in elite endurance runners.  Methods: The study has a crossover design in University laboratory. Eight elite male runners (Mean±SD age: 24.50±3.96 years; Mean±SD height: 179.75±4.62 cm; Mean±SD body mass: 67.37±3.42 kg; Mean±SD body mass index: 20.85±1.11 kg/m²) took part in the research. After 4 weeks of Living-Low (LL), the athletes performed 4 weeks Training-High (TH) and then, 3 weeks training-low (TL). Main Outcome Measures: Anthropometric parameters, time trial (1500 m), PGC-1α, and HIF-1α levels were measured in four different time points: pre-LL, post-LL, post-TH, and post-TL.  Results: There were no significant differences between the 4 time points for body mass and body mass index (P>0.05). The time trial was improved significantly (p <0.001) at post-TH as well as post-TL compared with the pre-LL and post-LL. TH decreased HIF-1α level but did not affect PGC-1α. Besides, TL increased both HIF-1α and PGC-1α.  Conclusion: Training at altitude reduces HIF-1α and training at sea-level increased PGC-1α and HIF-1α levels. Both types of training induced an improvement in the time trial. Athletes and coaches seek advice on the effective training strategy to enhance performance at different altitudes.